1997
DOI: 10.1021/jm960562m
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of a Cyclic Dynorphin A Analog Bound to Dodecylphosphocholine Micelles by NMR and Restrained Molecular Dynamics

Abstract: The compound c[Cys5,11]dynorphin A-(1-11)-NH2, 1, is a cyclic dynorphin A analog that shows similar selectivity and potency at the kappa-opioid receptor when compared to the native form of the peptide in central nervous system assays. Previous molecular mechanics calculations have shown that the ring portion of the isoform that is trans about the Arg9-Pro10 omega bond contains either a beta-turn from residues Arg6 to Arg9 or an alpha-helical conformation. Our results from solution state NMR indicate that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Opioid peptides have often been studied in media similar to the membrane environment, usually aqueous micellar solutions. The micelles generally used are based on SDS, a detergent easy to find in perdeuterated form [26][27][28][29], but there are also published studies of micelles of phospholipids [30][31][32][33][34][35][36].…”
Section: Membranesmentioning
confidence: 99%
“…Opioid peptides have often been studied in media similar to the membrane environment, usually aqueous micellar solutions. The micelles generally used are based on SDS, a detergent easy to find in perdeuterated form [26][27][28][29], but there are also published studies of micelles of phospholipids [30][31][32][33][34][35][36].…”
Section: Membranesmentioning
confidence: 99%
“…In bovine prothrombin, it was found that the cis X-Pro 22 conformer is essential to creating the membrane-binding conformation of prothrombin. 13,14 Tessmer et al 36 showed that for a cyclic dynorphin A analogue, the interaction with the DPC micelles stabilized the trans proline isomer (Arg-Pro). This is contrary to our result that shows that DPC does not affect the trans-cis equilibrium in the 11-24 segment of ACTH.…”
Section: Factors Affecting the Trans/cis Isomerismmentioning
confidence: 99%
“…Identification and structural characterization of selective opioid peptide ligands for the δ receptor (e.g. DPDPE [11], JOM‐13 [12]) and the κ receptor (dynorphin [13, 14]) have allowed modeling studies to begin for these types, but to date, few such studies for μ‐selective peptide ligands ( d ‐TIPP‐NH 2 ) have been reported [15].…”
Section: Introductionmentioning
confidence: 99%